Preparation method and application of poly-citric acid-based viscous composite coating
By preparing a polycitric acid-based adhesive composite coating on the Zn-based biodegradable metal surface, the problem of insufficient adhesion of the coating in the prior art is solved, firm binding with the matrix and antibacterial effect are achieved, and it is suitable for bone repair applications.
Patent Information
- Application Number
- CN202411318808.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-21
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-21
AI Technical Summary
The existing Zn-based biodegradable metal coating has low adhesion and is easy to fall off during actual use, and cannot effectively deal with complex bone defect environments.
Using the preparation method of polycitric acid-based viscous composite coating, acrylic acid and polylysine are added to the reaction system for preparing polycitric acid prepolymer to form double bond polycitric acid prepolymer and heat curing. Polycitric acid-based adhesive composite coating improves adhesion between the coating and the substrate.
It significantly improves the adhesion between the polycitric acid-based adhesive composite coating and the matrix, enhances antibacterial ability and cell adhesion, and ensures stability and effectiveness in bone repair.
Smart Images

Figure CN119185655A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of degradable biomedical materials, and in particular relates to a preparation method and application of a polycitric acid-based adhesive composite coating. Background Art
[0002] In recent years, Zn and its alloys have become biodegradable metals that have attracted much attention after magnesium and iron-based metals due to their good corrosion resistance and mechanical properties, and have now begun to be used in the field of bone repair. However, compared with the research and application in the industrial field over the years, the research on Zn-based biodegradable metals in the biological field is still in its infancy. Especially for the complex bone defect environment, single-function Zn metals cannot achieve satisfactory therapeutic effects. Therefore, it is particularly important to study how to improve the multifunctional properties of Zn metal so that it can effectively cope with the complex bone defect environment.
[0003] At present, the main approach to improve the multifunctional properties of Zn metal is to construct a coating with appropriate corrosion behavior and good biocompatibility on the surface of Zn metal. For example, constructing a phosphate conversion film on the surface of Zn metal can improve the viability, adhesion and proliferation of pre-osteoblastic cells, while inhibiting the adhesion of Escherichia coli. For example, preparing a protective film rich in calcium phosphate on the surface of Zn-1.5Mg alloy can improve the viability and adhesion of U-2OS cells. For example, a dexamethasone-loaded ZnO nanotube composite coating was prepared on a Zn metal substrate by anodization and silk / graphene self-assembly. This composite coating enhances biocompatibility and antibacterial properties due to the synergistic release of Zn ions and drugs during the degradation process. However, the adhesion between the above coatings and the substrate is low, and there is a problem of easy detachment during actual use. Summary of the invention
[0004] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and provide a method for preparing a polycitric acid-based adhesive composite coating. The preparation method comprises adding acrylic acid to a reaction system for preparing a polycitric acid prepolymer to generate a double-bond polycitric acid ester prepolymer, reacting with polylysine to form a polycitric acid ester composite solution, and thermally curing to form a polycitric acid-based adhesive composite coating. The polycitric acid-based adhesive composite coating has strong adhesion to the substrate, thus solving the problem that the prior art coating has low adhesion to the substrate and is easy to fall off during actual use.
[0005] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing a polycitric acid-based adhesive composite coating, characterized in that the preparation method comprises the following steps:
[0006] Step 1, after citric acid is melted under nitrogen protection, polyethylene glycol and 1,8-octanediol are added, acrylic acid is then added dropwise and stirred under vacuum conditions, and dissolution, dialysis purification and vacuum freeze drying are performed in sequence to obtain a double-bond polycitrate prepolymer;
[0007] Step 2: mixing polylysine with the double-bond polycitrate prepolymer obtained in step 1 to obtain a polycitrate composite solution;
[0008] Step 3: dripping the polycitrate composite solution obtained in step 2 onto the surface of the substrate and spreading it, and then thermally curing it to obtain a polycitrate-based adhesive composite coating.
[0009] The invention can improve the antibacterial ability of the polycitric acid-based adhesive composite coating by adding polylysine, and polylysine has a binding site, which can improve the adhesion of the polycitric acid-based adhesive composite coating to the substrate and cells.
[0010] The above-mentioned method for preparing a polycitric acid-based adhesive composite coating is characterized in that the melting temperature in step 1 is 160°C, and the temperature when adding acrylic acid is 130°C.
[0011] The present invention adjusts the temperature to 130° C. to prevent the reaction system from solidifying when the temperature is lower than 130° C. and to prevent a large amount of acrylic acid from volatilizing when the temperature is higher than 130° C.
[0012] The above-mentioned method for preparing a polycitric acid-based adhesive composite coating is characterized in that the molar ratio of citric acid to acrylic acid in step one is 1:1.
[0013] The above-mentioned method for preparing a polycitrate-based adhesive composite coating is characterized in that the concentration of the polylysine in the polycitrate composite solution in step 2 is 1 mg / mL to 2 mg / mL, and the mass concentration of the double-bond polycitrate prepolymer in the polycitrate composite solution is 1% to 15%.
[0014] The invention controls the concentration of polylysine and double-bond polycitrate prepolymer in the polycitrate composite solution to avoid cytotoxicity due to too high concentration and to avoid weakening of the biological function of the polycitrate-based adhesive composite coating due to too low concentration.
[0015] The method for preparing the above-mentioned polycitrate-based adhesive composite coating is characterized in that bioactive glass nanoparticles are added to the polycitrate composite solution in step 2.
[0016] The invention is used for enhancing the biological activity of the polycitrate-based adhesive composite coating by adding bioactive glass nanoparticles into the polycitrate composite solution.
[0017] The above-mentioned method for preparing a polycitrate-based adhesive composite coating is characterized in that the concentration of the bioactive glass nanoparticles in the polycitrate composite solution is 1 mg / mL to 2 mg / mL.
[0018] The above-mentioned method for preparing a polycitrate-based adhesive composite coating is characterized in that the amount of the polycitrate composite solution added in step three is 10 μL to 100 μL.
[0019] The above-mentioned method for preparing a polycitric acid-based adhesive composite coating is characterized in that the heat curing temperature in step three is 50° C. to 80° C., and the heat curing time is 2 h to 5 h.
[0020] In addition, the present invention also discloses the use of the polycitric acid-based adhesive composite coating, characterized in that the polycitric acid-based adhesive composite coating is used for bone repair.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] 1. The present invention generates a double-bond polycitrate prepolymer with excellent reactivity and functionality by adding acrylic acid into the reaction system for preparing the polycitric acid prepolymer, thereby introducing more cross-linking points and functional groups, which is beneficial to improving the adhesion between the polycitric acid-based adhesive composite coating and the substrate, so that it is not easy to fall off during use; at the same time, the polycitric acid-based adhesive composite coating can provide an acidic environment to accelerate the decomposition of the Zn substrate and increase the release rate of Zn ions.
[0023] 2. The polycitric acid-based adhesive composite coating prepared by the present invention can still have strong adhesion when the thickness of the polycitric acid-based adhesive composite coating reaches 60 μm or more, and can be firmly combined with the Zn substrate.
[0024] 3. The present invention adopts citric acid, acrylic acid and polylysine as raw materials to prepare the polycitric acid-based adhesive composite coating, which can greatly reduce the production cost, and the preparation process is simple and can be completed without complex equipment or harsh conditions, which effectively reduces the difficulty of technology promotion and industrial production.
[0025] 4. The present invention can control the function and thickness of the polycitric acid-based adhesive composite coating by precisely regulating the composition and concentration of each component in the polycitric acid ester composite solution. The polycitric acid-based adhesive composite coating has a large number of active sites and can attach multiple components to the surface of the substrate to prepare a polycitric acid-based adhesive composite coating with adjustable components and controllable performance. The polycitric acid-based adhesive composite coating has a high degree of customization and can be precisely designed according to different biomedical needs, opening up broad space for the application of Zn metal in diversified medical scenarios.
[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a graph showing the osteogenic performance test results of the polycitric acid-based adhesive composite coating, Zn and blank groups prepared in Example 1 of the present invention.
[0028] Figure 2 This is a microscopic morphology of Zn in Example 1 of the present invention.
[0029] Figure 3 This is a microscopic morphology of the polycitric acid-based adhesive composite coating prepared in Example 1 of the present invention.
[0030] Figure 4 This is a microscopic morphology of the polycitric acid-based adhesive composite coating prepared in Example 2 of the present invention.
[0031] Figure 5 This is a microscopic morphology of the side of the polycitric acid-based adhesive composite coating prepared in Example 1 of the present invention.
[0032] Figure 6 This is a microscopic morphology of the side of the polycitric acid-based adhesive composite coating prepared in Example 2 of the present invention.
[0033] Figure 7 1 is a graph showing the relationship between the acoustic signal, friction force and displacement of the polycitric acid-based adhesive composite coating prepared in Example 1 of the present invention.
[0034] Figure 8 4 is a graph showing the relationship between the acoustic signal and the probe pressure of the polycitric acid-based adhesive composite coating prepared in Example 1 of the present invention.
[0035] Fig. 9 4 is a graph showing the relationship between the acoustic signal, friction force and displacement of the polycitric acid-based adhesive composite coating prepared in Example 2 of the present invention.
[0036] Fig.10 4 is a graph showing the relationship between the acoustic signal and the probe pressure of the polycitric acid-based adhesive composite coating prepared in Example 2 of the present invention.
[0037] Fig.11 The graph is a hydrophilicity test result diagram of the polycitric acid-based adhesive composite coating and Zn prepared in Example 1 and Example 2 of the present invention.
[0038] Fig.12 This is a graph showing the 1d cell compatibility test results of the polycitrate-based adhesive composite coating, Zn and blank groups prepared in Examples 1 and 2 of the present invention.
[0039] Fig.13This is a 3D cell compatibility test result diagram of the polycitrate-based adhesive composite coating, Zn and blank group prepared in Example 1 and Example 2 of the present invention.
[0040] Fig.14 This is a graph showing the Zn ion release test results of the polycitric acid-based adhesive composite coating and Zn prepared in Example 1 and Example 2 of the present invention. DETAILED DESCRIPTION
[0041] Example 1
[0042] This embodiment includes the following steps:
[0043] Step 1, 4g of citric acid was melted at 160°C for 10min under nitrogen protection, and then 6.25g of polyethylene glycol and 1,8-octanediol were added, the temperature was lowered to 130°C, and then 1.5g of acrylic acid was added dropwise, and the mixture was vigorously stirred for 5h under vacuum conditions, and then dissolved, dialyzed and purified, and vacuum-freeze-dried in sequence to obtain a double-bond polycitrate prepolymer; the dialysis purification time was 3d;
[0044] Step 2: mixing polylysine with the double-bond polycitrate prepolymer obtained in step 1, and then adding bioactive glass nanoparticles to obtain a polycitrate composite solution; the concentration of the polylysine in the polycitrate composite solution is 1 mg / mL, the concentration of the bioactive glass nanoparticles in the polycitrate composite solution is 1 mg / mL, the mass concentration of the double-bond polycitrate prepolymer in the polycitrate composite solution is 1%, and the bioactive glass nanoparticles are Cu ion-doped bioactive glass nanoparticles;
[0045] Step 3: Add 100 μL of the polycitrate composite solution obtained in step 2 onto the Zn surface and spread it, and heat cure it at 50° C. for 3 h to obtain a polycitrate-based adhesive composite coating.
[0046] The polycitric acid-based adhesive composite coating obtained in this example is recorded as Zn@P1.
[0047] MC3T3-E1 osteoblasts were used to test the osteogenic performance of uncoated Zn and Zn@P1. According to the relevant provisions of "Biocompatibility Test" (ISO 10993), the extracts of uncoated Zn and Zn@P1 were prepared respectively; the extracts of uncoated Zn and Zn@P1 were diluted to 25 times and co-cultured with MC3T3-E1 osteoblasts for 28 days. The results of calcium deposition (CAL) and collagen secretion (COL) are shown in Figure 2. Figure 1As shown, compared with Ctrl (representing co-culture with MC3T3-E1 osteoblasts under blank cell culture plate conditions), the calcium deposition of Zn and Zn@P1 was increased, among which the error bar of the calcium deposition of Zn@P1 was shorter and the calcium deposition was more uniform; compared with Ctrl and Zn, Zn@P1 showed a higher collagen secretion value; in summary, it is shown that the polycitrate-based adhesive composite coating prepared in this example has a good osteogenic effect.
[0048] Example 2
[0049] The difference between this embodiment and embodiment 1 is that in step 2, the mass concentration of the double-bond polycitrate prepolymer in the polycitrate composite solution is 5%.
[0050] The polycitric acid-based adhesive composite coating obtained in this example is recorded as Zn@P5.
[0051] The morphology of uncoated Zn, Zn@P1 and Zn@P5 was characterized. The surface morphology features are as follows: Figures 2 to 4 As shown in the figure, there are obvious scratches on the Zn surface, a large number of bioactive glass nanoparticle aggregates can be observed on the surface of Zn@P1, the surface of Zn@P5 is smoother than that of Zn@P1, and both Zn@P1 and Zn@P5 can be evenly attached to the Zn surface; the side morphology of Zn@P1 and Zn@P5 was also characterized, as shown in the figure. Figure 5 and Figure 6 As shown, the thickness of Zn@P1 was measured to be 25.70 μm, and the thickness of Zn@P5 was measured to be 66.99 μm, indicating that the preparation method of the present invention can adjust the thickness of the polycitric acid-based adhesive composite coating by adjusting the concentration of the double-bond polycitric acid ester prepolymer.
[0052] The coating adhesion of Zn@P1 and Zn@P5 was tested using a nano scratch tester. The results are as follows: Figures 7 to 10 As shown, the critical bonding force (Fc) of the coating was determined based on the mutation points of the acoustic signal and the friction force, and the coating adhesion of Zn@P1 was 5004.56 mN and the coating adhesion of Zn@P5 was 4115.36 mN, indicating that the polycitric acid-based adhesive composite coating has strong adhesion on the Zn surface.
[0053] The hydrophilicity test of Zn@P1 and Zn@P5 was carried out using a water contact angle meter. The results are as follows: Fig.11 As shown in the figure, compared with Zn, both Zn@P1 and Zn@P5 have good hydrophilicity, and the surface water contact angles of Zn@P1 and Zn@P5 decrease continuously with time.
[0054] MC3T3-E1 osteoblasts were used for cell compatibility testing. According to the relevant provisions of "Biocompatibility Testing" (ISO10993), extracts of uncoated Zn, Zn@P1 and Zn@P5 were prepared, and then the extracts were diluted to 25 times and 50 times (respectively recorded as x25 and x50). The extracts diluted to 25 times and 50 times were co-cultured with MC3T3-E1 osteoblasts for 1 day and 3 days, respectively. The results are shown in Figure 2. Fig.12 and Fig.13 As shown (Ctrl indicates co-culture with MC3T3-E1 osteoblasts under blank cell culture plate conditions), the extracts of each group showed good cell activity after co-culture with MC3T3-E1 osteoblasts for 1d and 3d, indicating that the polycitrate-based adhesive composite coating has good compatibility with osteoblasts.
[0055] The uncoated Zn, Zn@P1 and Zn@P5 were immersed in DMEM cell culture medium for 24 h, and the Zn ion release was tested. Fig.14 As shown, compared with the uncoated Zn, the Zn ion release in the immersion solution of Zn@P1 and Zn@P5 was higher, both exceeding 370 mg / L, indicating that the polycitrate-based adhesive composite coating can significantly increase the release of Zn ions.
[0056] Example 3
[0057] The difference between this embodiment and embodiment 1 is that: in step 2, the concentration of polylysine in the polycitrate composite solution is 2 mg / mL, the concentration of bioactive glass nanoparticles in the polycitrate composite solution is 2 mg / mL, and the mass concentration of double-bond polycitrate prepolymer in the polycitrate composite solution is 15%; in step 3, 90 μL of the polycitrate composite solution is added dropwise to the Zn surface and spread, and thermally cured in an environment of 60°C for 5 hours.
[0058] After testing, the thickness of the citric acid-based adhesive composite coating prepared in this embodiment is 200.01 μm, and the coating adhesion is 4500.00 mN.
[0059] Example 4
[0060] The difference between this embodiment and embodiment 3 is that in step 3, 10 μL of the polycitrate composite solution is dripped onto the Zn surface and spread, and thermally cured in an environment of 80° C. for 2 h.
[0061] After testing, the thickness of the citric acid-based adhesive composite coating prepared in this embodiment is 46.12 μm, and the coating adhesion is 4710.21 mN.
[0062] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a polycitric acid-based adhesive composite coating, characterized in that: The preparation method comprises the following steps: Step 1, after citric acid is melted under nitrogen protection, polyethylene glycol and 1,8-octanediol are added, acrylic acid is then added dropwise and stirred under vacuum conditions, and dissolution, dialysis purification and vacuum freeze drying are performed in sequence to obtain a double-bond polycitrate prepolymer; Step 2: mixing polylysine with the double-bond polycitrate prepolymer obtained in step 1 to obtain a polycitrate composite solution; Step 3: drop the polycitrate composite solution obtained in step 2 onto the surface of the substrate and spread it, and then perform thermal curing to obtain a polycitrate-based adhesive composite coating.
2. The method for preparing a polycitrate-based adhesive composite coating according to claim 1, characterized in that: The melting temperature in step 1 is 160°C, and the temperature when adding acrylic acid dropwise is 130°C.
3. The method for preparing a polycitrate-based adhesive composite coating according to claim 1, characterized in that: The molar ratio of citric acid to acrylic acid in step 1 is 1:
1.
4. The method for preparing a polycitrate-based adhesive composite coating according to claim 1, characterized in that: In step 2, the concentration of the polylysine in the polycitrate composite solution is 1 mg / mL to 2 mg / mL, and the mass concentration of the double-bond polycitrate prepolymer in the polycitrate composite solution is 1% to 15%.
5. The method for preparing a polycitric acid-based adhesive composite coating according to claim 1, characterized in that: In step 2, bioactive glass nanoparticles are added to the polycitrate composite solution.
6. The method for preparing a polycitric acid-based adhesive composite coating according to claim 5, characterized in that: The concentration of the bioactive glass nanoparticles in the polycitrate composite solution is 1 mg / mL to 2 mg / mL.
7. The method for preparing a polycitric acid-based adhesive composite coating according to claim 1, characterized in that: The amount of the polycitrate composite solution added in step 3 is 10 μL to 100 μL.
8. The method for preparing a polycitric acid-based adhesive composite coating according to claim 1, characterized in that: The heat curing temperature in step 3 is 50° C. to 80° C., and the heat curing time is 2 h to 5 h.
9. Use of a polycitric acid-based adhesive composite coating prepared according to any one of claims 1 to 8, characterized in that: The polycitrate-based adhesive composite coating is used for bone repair.
Citation Information
Patent Citations
Degradable silica-based hybrid polymer biomedical elastomer and preparation method thereof
CN105504251A
Bioactive composite material as well as preparation method and application thereof
CN108530851A
NHS (N-hydroxysuccinimide) active ester modified poly-citrate as well as preparation method and application thereof
CN116693834A
Photocuring bioactive poly-citrate-based polyurethane medical adhesive and preparation method thereof
CN117224730A
Active PEEK implant material for high osseointegration and bone repair as well as preparation method and application of active PEEK implant material
CN117343333A
